Effect of Surface Layers in Sliding Contact of Viscoelastic Solids (3-D Model of Material) - Torskaya, Elena V.; Stepanov, Fedor I. (Frontiers in Mechanical Engineering, 2019)
Sliding contact of a smooth indenter and a two-layered half-space is considered taking into account rheological properties of materials. The case of a viscoelastic layer bonded with a rigid half-space is analyzed as well as an opposite one, which is viscoelastic half-space covered by rigid layer. The problem is formulated as quasi-static. Numerical-analytical method of solution is based on boundary element method and iteration procedure. New analytical solution is used to calculate influence coefficients for the computation procedure. Contact pressure, energy dissipation and internal stresses are analyzed in dependence on sliding velocity, layer thickness and Poisson's ratio.